PERAN CAMAT DALAM MENINGKATKAN KINERJA APARATUR DESA - Aminnullah ' (Universitas Riau, 2015)
The role of Head of the Apparatus Improve Performance village. This study aims to determine the role of Head of the Apparatus Improve the Performance of the village in the district of the Coastal Rangsang Meranti Islands regency and factors mempengaruhinya.Metode used in this research is qualitative descriptive method. Informants research is Head, Sekcam, village head, village secretary and village Apparatus. Pegumpulan techniques of data is through interviews, observation and documentation. Data analysis techniques in this study using qualitative research model consisting of data reduction, data presentation and withdrawal kesimpulan.Hasil these studies show that the role of Head in improving the performance of the apparatus coastal villages in the district Rangsang KabupatenKepulauan Meranti generally been implemented in accordance with the basic tasks, functions and camat authority to run the government.